Definition, history of denim fabric and Turkey's denim clothing export in figures - (:unkn) unknown (INST NATL CERCETARE-DEZVOLTARE TEXTILE PIELARIE-BUCURESTI, 2018)
This study examines the definition of denim fabric, its historical development in Turkey and in global and product and country based export data of denim clothing of the recent 15 years of export of Turkey which has rapidly risen and become a very important market amongst related countries in the world.
Keywords: denim; history of denim fabric; denim clothing; denim exports